Gambaran indikasi ibu bersalin dengan tindakan seksio caesarea - Estu Rinukti; Sujiyatini Sujiyatini; Nur Djanah (Poltekkes Kemenkes Yogyakarta, 2015)
The Sectio Caesarea (SC) has various benefits of labor but also increases the risk of complications and death. The amount of labor of SC in Panti Rapih hospital to mess with an increase from 2009 until 2011. This research aims to know the birthing mother with the indication of SC in Panti Rapih Hospital Yogyakarta in 2011. This research is a descriptive study with a survey design. The sample is the entire birthing mothers with SC recorded in the medical record in Panti Rapih Hospital Presentable in 2011 as much as 593. Instrument-collecting data using the format research, analyzed by descriptive. the results showed the characteristics of maternity mother with SC in Panti Rapih hospital Yogyakarta in 2011 is a healthy reproductive age majority (84,0%) and parity-risk (59,9o/o). The majority of SC based on indications of the mather factor is APS (45.3%), whereas fetal factors are based on the layout of the breach (32.9%). Summary indication of SC in Panti Rapih hospital in 2011 based on maternal factors most heavily upon request and based on the factors in the fetal position of the breech.